Strategi Pengembangan Potensi Wisata Desa Dalam Meningkatkan Daya Tarik Wisatawan Di Desa Cimanggu Kecamatan Langkaplancar Kabupaten Pangandaran - Lisna Sari; H. Otong Husni Taufiq; R. Rindu Garvera (Journal of Research and Development on Public Policy, 2024)
Developing village tourism potential is an important strategy in increasing tourist attraction. The villages have unique cultural, natural and traditional riches, which can be a major attraction for tourists. This research aims to examine the role of developing village tourism potential in increasing tourist attraction. The research method used is literature study and secondary data analysis. The research results show that developing village tourism potential involves various aspects, such as preserving local culture, infrastructure development, tourism promotion, and involvement of local communities. Developing village tourism potential can provide double benefits, namely increasing the income and welfare of village communities while maintaining the ecosystem and culture. With the right efforts, villages can become attractive tourist destinations for tourists, both domestic and international. This research underlines the importance of collaboration between government, the private sector and local communities in developing village tourism potential. In addition, effective tourism promotion and careful planning are very important in increasing the attractiveness of villages as tourist destinations.